(untitled) (Research, Society and Development, 2020)
The study aimed to know the perceptions of puerperae about the obstetric interventions experienced during the parturition process. This is a qualitative research, carried out with 14 puerperas assisted in Family Health Strategies of the urban area of a municipality on the western border of Rio Grande do Sul, Brazil. Data generation occurred through semi-structured interviews. The data were analyzed according to Minayo’s operational proposal. The research followed the ethical precepts of investigations with human beings. The parturition process was negatively experienced due to exposure to undesired and aggressive situations, imposed through actions of health professionals, which may be characterized as obstetric violence. Such violence may be evidenced by Kristeller’s maneuver, use of forceps and episiotomy, without consent or knowledge on the part of women. Practices useful in childbirth are still poorly implemented, while other harmful or ineffective practices continue to be performed.